Analysis of Students' Satisfaction Level on iLearn Quality during COVID-19 Pandemic with WebQual 4.0 and PLS-SEM - HG, Izzati Rahmi; Wulandari, Frilianda; Devianto, Dodi (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Andalas University implements a Learning Management System (LMS) named iLearn as an online learning facility to carry out the learning process during the COVID-19 pandemic. This research analyzes the influence of iLearn quality on students' satisfaction levels. iLearn quality is measured by WebQual 4.0 instrument, which consists of three variables, i.e. Usability, Information Quality, and Service Interaction Quality. To analyze the relationship between the WebQual 4.0 variables and students' satisfaction, we used Partial Least Squares - Structural Equation Modeling (PLS-SEM) method. The research sample is 100 students of the Mathematics Department of Andalas University who were enrolled in iLearn. Based on data analysis, the structural equation model for the students' satisfaction level is obtained. From the model, the variables that significantly affect the Student Satisfaction Level are Usability and Service Interaction Quality, with a P-value of 0.001. In contrast, the Information Quality has a low significance in influencing students' satisfaction levels in iLearn quality with a P-value of 0.420. Improvements on iLearn quality can be made by reviewing these measured indicators.